PENGARUH MEDIA BONEKA TANGAN TERHADAP KEMAMPUAN MENYIMAK ISI DONGENG MATA PELAJARAN BAHASA JAWA SISWA SEKOLAH DASAR - - Rumidjan; Muhana Gipayana (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2013)
Abstract: Effect of Hand Puppet on Elementary School Students’ Listening Story Content Skills in Javanese Language Subject. Purpose of this research was to describe; (1) elementary school students listening story content skills in the javanese language subject, (2) process of listening story content in the javanese language subject, (3) Effect of hand puppet on elementary school students listening story content skills in a javanese language subject. Research subjects were elementary school’ students Class IIA (control group) and elementary school’ students Class IIA (experiment group). Data was collected using experiment technique. Data analysis used t-test. Research result showed there were a difference in learning achievement among class II students who were following learning with the hand puppet media and students who were following learning without the hand puppet media.Abstrak: Penelitian ini bertujuan mendeskripsikan: (1) kemampuan menyimak isi dongeng mata pelajaran Bahasa Jawa, (2) proses menyimak isi dongeng mata pelajaran Bahasa Jawa, dan (3) pengaruh penggunaan media boneka tangan terhadap kemampuan menyimak dongeng mata pelajaran Bahasa Jawa. Subyek penelitian ini adalah siswa SD kelas IIA (kelompok kontrol) dan siswa SD kelas IIB (kelompok eksperimen). Data dikumpulkan dengan menggunakan teknik eksperimen. Analisis data menggunakan teknik uji-t. Hasil penelitian menunjukkan perbedaan hasil belajar kemampuan menyimak isi dongeng Bahasa Jawa yang signifikan antara siswa kelas II yang mengikuti pembelajaran menggunakan media boneka tangan dengan yang mengikuti pembelajaran tanpa menggunakan media boneka tangan.Kata Kunci: menyimak isi dongeng, media boneka tangan, SD